Rosiglitazone-loaded Nanospheres for Modulating Macrophage-Specific Inflammation in obesity - Di Mascolo, Daniele (2013)
PPARγ nuclear receptor agonists have been shown to attenuate macrophage inflammatory responses implicated in the metabolic complications of obesity and in atherosclerosis. However, PPARγ agonists currently in clinical use, including rosiglitazone (RSG), are often associated with severe side effects that limit their therapeutic use. Here, 200 nm PLGA/PVA nanospheres were formulated for the systemic delivery of RSG specifically to macrophages. RSG was encapsulated with over 50% efficiency in the hydrophobic PLGA core and released specifically within the acidifying macrophage phagosomes. In bone marrow derived macrophages, RSG-loaded nanoparticles (RSG-NPs) induce a dose dependent upregulation (1.5 to 2.5-fold) of known PPARγ target genes, with maximal induction at 5 μM; and downregulate the expression of genes related to the inflammatory process, with maximum effect at 10 μM. In Ldlr(-/-) mice fed high fat diet, treatment with RSG-NPs alleviated inflammation in white adipose tissue and liver but, unlike treatment with free RSG, did not alter genes associated with lipid metabolism or cardiac function, indicating a reduction in the RSG side effect profile. These biocompatible, biodegradable RSG-NPs represent a preliminary step towards the specific delivery of nuclear receptor agonists for the treatment of macrophage-mediated inflammatory conditions associated with obesity, atherosclerosis and other chronic disease states.